Comparison of two commercial broth microdilution panels for multidrug-resistant Gram-negative bacteria: Thermo Scientific™ Sensititre DKMGN vs. Beckman Coulter MicroScan NMDRM1 - Aupaix, Antoine; Lamraoui, Kamila; Rodriguez-Villalobos, Hector; Anantharajah, Ahalieyah; Verroken, Alexia (Frontiers in Microbiology, 2024)
Two commercial broth microdilution panels for testing of multidrug-resistant Gram-negative bacteria were compared, Thermo Scientific TM Sensititre DKMGN and Beckman Coulter NMDRM1, for seventeen antimicrobial agents. Two hundred and seven isolates were tested: 3 ATCC and 1 NCTC strain, 6 quality control strains from the Belgian National Antimicrobial committee and 197 clinical isolates, including carbapenem-resistant Enterobacterales, Pseudomonas aeruginosa and Acinetobacter baumannii.EUCAST 2023 breakpoints version 13.1 was used to assign susceptibility category. Overall categorical (CA) and essential agreements (EA) were above 90% but several useful antibiotics for the treatment of multi-resistant organisms showed CA and EA under 90%, i.e. meropenem, imipenem and colistin for Enterobacterales and meropenem and colistin for P. aeruginosa. Regarding Enterobacterales, the NMDRM1 panel gave significantly higher resistance rate with meropenem, imipenem, amikacin and colistin. For carbapenems, the minimal inhibitory concentrations (MIC) were underestimated by the DKMGN panel, as already pointed out by a warning on the EUCAST website. For a better assessment of carbapenem susceptibilities in carbapenem-resistant organisms, the use of a higher inoculum is now required in the insert kit of DKMGN panel. However, for a given isolate whose susceptibility to carbapenems is not known, there is a risk of underestimating the MIC values. Our results showed that colistin testing remains a challenge and more accurate commercial methods should be developed urgently. The use of a single commercial method cannot guarantee a good precision in the determination of the MIC value for colistin.